Experiences of interreligious encounter at religiously affiated hospital: Striving to build amicable interreligious relationship through healthcare service in Yogyakarta context - Jekonia Tarigan; Heddy Shri Ahimsa-Putra; Leonard Chrysostomos Epafras (UNHI PRESS, 2021)
This paper aims to examine the interreligious encounter experiences of patients and their families who have diverse religious backgrounds and come to religiously affiliated hospitals (different from their religion). The main question raised is how this experience strengthens their recognition and respect toward other religions, so they are enabled to build amicable interreligious relations. This study is necessary especially in the context of Yogyakarta, which claims itself as ‘City of Tolerance,’ but unfortunately, this claim and image have faded because of many cases of intolerance in multiple social settings, such as school, campus, worship place, religious event, boarding house, even also cemetery. Meanwhile, in Yogyakarta, three major religiously affiliated hospitals have served Yogyakarta residents for tens to hundreds of years, namely Bethesda, Panti Rapih, and PKU Muhammadiyah Yogyakarta. Following Peter L. Berger, this paper argues that hospital can be seen as a unique social setting, in which pluralism as empirical experience truly happens because, in terms of attitude, the hospital is an institution that is in its service should practice no discrimination toward people from a different background (ethnicity or religiosity) related to service for humanity. Therefore hospital will be a place of encounter for people from various backgrounds and identities. Within the religiously affiliated hospital, pluralism is not only a formal philosophical concept but a social situation in which people with different ethnicities, religions, worldviews, and moralities live together peacefully and interact with each other amicably.